An investigation of the effect of intermediate layer in three-component planar photonic crystal waveguides - Shen, Hongjun; Tian, Huiping; Ji, Yuefeng (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
The introduction of a third component into planar photonic crystal waveguides definitely influences the properties of linear defect modes, such as the band diagram, intrinsic loss, group velocity and group velocity dispersion. With the increase of the dielectric constant of the interlayer, the guided modes shift to lower frequencies and the radiative losses decrease in the frequency region of high group velocity of defect mode. The analysis of the sensitivity of a band diagram to the introduction of an interlayer reveals that the wider the planar photonic crystal waveguide and the thicker the slab, the more tolerant the overall structure. When one designs the real planar photonic crystal waveguides, the effect of unintentional intermediate layer on the optical properties of planar photonic crystal waveguides has to be taken into consideration. At the same time, the introduction of an intentional interlayer into macroporous planar photonic crystal waveguides can be utilized to optimize the design.
Optica Applicata, Vol. 39, 2009, nr 2, s. 295-306
Keywords: optyka; three-component planar photonic crystal waveguide; intermediate layer; group velocity; group velocity dispersion